Sol-gel coatings for electrical gas sensors - Kozłowska, Katarzyna; Łukowiak, Anna; Szczurek, Andrzej; Dudek, Krzysztof; Maruszewski, Krzysztof (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
The influence of volatile organic compound vapours of TiO2 gas-sensing layers prepared via the sol-gel technique was investigated. The sol-gel-derived layers were tested in the environment of alcohols, aliphatic and aromatic compounds. Specified organic compounds caused reversible changes of the semiconductor film resistance. The response of the titania film was registered as current intensity changes versus time at different sensor operating temperatures. The results suggested that TiO2 films prepared by the sol-gel technique can be used as chemical sensors.
Optica Applicata, Vol. 35, 2005, nr 4, s. 783-790
Keywords: optyka; gas sensor; sensor; sol-gel layer; sol-gel technology